2020
DOI: 10.3390/mi11080756
|View full text |Cite
|
Sign up to set email alerts
|

Parallel-Channel Electrotaxis and Neuron Screening of Caenorhabditis elegans

Abstract: In this paper, we report a novel microfluidic method to conduct a Caenorhabditis elegans electrotaxis movement assay and neuronal imaging on up to 16 worms in parallel. C. elegans is a model organism for neurodegenerative disease and movement disorders such as Parkinson’s disease (PD), and for screening chemicals that alleviate protein aggregation, neuronal death, and movement impairment in PD. Electrotaxis of C. elegans in microfluidic channels has led to the development of neurobehavioral screening platforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Prior to EF stimulation, a 60 s acclimation period was used during which the flow was stopped by maintaining the inlet and outlet tubes at the same height level. Our previous experiments showed that the anode-facing worms could deposit significantly more eggs 27,35 , highlighting that the worm loading orientation with respect to the EF direction could affect our results. To maintain an equal exposure condition among randomly oriented worms in our device (as shown in Figure 2A), we adopted a new EF stimulation technique in which a series of 5s anodal and 5s cathodal pulses, separated by 25s acclimation periods, was applied for 10 min (Figure 2B).…”
Section: Methodsmentioning
confidence: 76%
See 2 more Smart Citations
“…Prior to EF stimulation, a 60 s acclimation period was used during which the flow was stopped by maintaining the inlet and outlet tubes at the same height level. Our previous experiments showed that the anode-facing worms could deposit significantly more eggs 27,35 , highlighting that the worm loading orientation with respect to the EF direction could affect our results. To maintain an equal exposure condition among randomly oriented worms in our device (as shown in Figure 2A), we adopted a new EF stimulation technique in which a series of 5s anodal and 5s cathodal pulses, separated by 25s acclimation periods, was applied for 10 min (Figure 2B).…”
Section: Methodsmentioning
confidence: 76%
“…This prevented the use of unidirectional pulses because approximately half of the worms would have been exposed to cathodal pulses, leading to no egg-laying response and waste of animals. Similar longitudinal orientation in the multi-worm device may have been achieved by preconditioning the worms with a longitudinal stimulus (e.g., controlled EF 37 or flow 38 ), but this would have added complexity to our procedures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, various types of micro- and nano-structures play important roles in advanced bioimaging applications. Accordingly, in this Editorial, we highlight reviews and original research articles that focus on the use of micromachining for advanced biological imaging, including in micro-optics [ 1 , 2 , 3 ], nanopatterning [ 4 , 5 ], and optical imaging with microfluidics [ 6 , 7 , 8 ].…”
mentioning
confidence: 99%
“…This is a simple and inexpensive method that can be performed on a conventional fluorescence microscope that uncouples the observation and selection of droplets. Youssef et al report the development of an easy-to-use microfluidic electrotaxis-based chip that can be used to investigate the behavior and neuron degeneration of 16 worms in parallel [ 8 ]. They show its applicability for genetic, chemical, and neuronal screening after validating it against a single-worm electrotaxis assay.…”
mentioning
confidence: 99%